Story solutions using tales to build character and teach bully prevention, drug prevention, and conflict resolution - Strauss, Kevin 1969- (Santa Barbara, Calif. Libraries Unlimited, 2011)
This book contains "background information, traditional stories, and skill-building activities that will enable librarians and other educators to help their students master bullying and drug prevention, self-control, and conflict resolution, as well as establish health self-esteem and optimism."--Back cover.
Crash course in storytelling (for librarians, parents, and other educators) -- Blocking and preventing bullying behavior -- Bully prevention stories -- Bully-stopper self-defense techniques -- Alcohol, tobacco, and other drugs suck -- Drug abuse prevention stories -- Drugs suck activities -- Conflict resolution facts -- Conflict resolution stories -- Conflict resolution activities.
Keywords: Storytelling; Problem solving in children; Conflict management